Forensic approach in cases of anabolic-androgenic steroid abuse and cardiovascular mortality: insights from autopsy, histopathology, immunohistochemistry and toxicology - Di Fazio, Nicola; Volonnino, Gianpietro; Treglia, Michele; Delogu, Giuseppe; Bubbico, Tommaso; Rinaldi, Raffaella; La Russa, Raffaele; Maiese, Aniello (Frontiers in Cardiovascular Medicine, 2025)
The abuse of anabolic-androgenic steroids (AAS) is associated with numerous adverse cardiovascular effects, including ventricular hypertrophy, myocardial fibrosis, and sudden cardiac death (SCD), which is a term that identifies a sudden death occurred due to cardiac conditions, congenital or acquired, particularly among young athletes and bodybuilders. This systematic review examines cases of AAS-related deaths, with a particular focus on autoptic, histopathological, immunohistochemical, and toxicological findings that highlight cardiac remodeling and myocardial damage. Numerous fatal cases were analyzed, primarily involving young men with a history of AAS abuse. Autopsy examinations revealed significant cardiac abnormalities such as left ventricular hypertrophy, coronary thrombosis, and dilated cardiomyopathy. Histopathological analyses showed focal myocardial necrosis, myocardial fiber disarray, and interstitial fibrosis, while immunohistochemical studies confirmed the presence of markers such as troponin T, fibronectin, and the C5b-9 complement complex, indicating inflammation, fibrosis, and necrosis. Toxicological analyses frequently detected testosterone, stanozolol, trenbolone, and nandrolone in blood, urine, and hair samples, confirming prolonged use of these substances. The results suggest that AAS-induced hypertrophy and fibrosis contribute to the pathogenesis of fatal arrhythmias and sudden cardiac death, even in the absence of pre-existing coronary artery disease. This review highlights the importance of integrating histopathological, immunohistochemical, and toxicological analyses with autopsy findings in forensic investigations to accurately identify AAS-related deaths and develop prevention strategies to reduce the abuse of these substances, particularly among young athletes and bodybuilders.